Effect of the annealing conditions on the structural stability and photoelectrical properties of wurtzite structured Cu2ZnSnS4 nanoparticles. (December 2015) - Zhang, Qing; Cao, Meng; Shen, Jie Sheng; Huang, Jian; Zhao, Yue; Sun, Yan; Wang, Lin Jun; Shen, Yue
Abstract: Wurtzite Cu2 ZnSnS4 (CZTS) nanoparticles with bandgaps of about 1.53 eV were synthesized by a simple solvothermal method with ethanediamine (En) as the reaction solvent. The effect of the annealing conditions on the structural stability and photoelectrical properties of wurtzite structured CZTS nanoparticles was detailedly studied. Raman spectra and X-ray photoelectron spectroscopy studies indicated that wurtzite CZTS would be changed to kesterite CZTS with the increasing of annealing temperature from 500 °C to 600 °C, no matter what annealing condition was adopted. But no secondary phases were found when the annealing atmosphere was N2 /H2 S (5%). Some secondary phases, such as CuS, Cu3 SnS4 or Cu4 SnS4, were found when CZTS nanoparticles were annealed in N2 atmosphere or vacuum. Annealing process could enhance the photoelectrical properties of CZTS nanoparticle thin films, especially when they were annealed in N2 /H2 S (5%). Highlights: Wurtzite CZTS has better structural stability under the annealing condition of N2 /H2 S (5%). CZTS can keep phase purities when they are annealed in N2 /H2 S (5%). All the annealing process can enhance the optoelectric properties of wurtzite CZTS.